Frequency domain analysis of a hybrid aquaculture-wind turbine offshore floating system - Abhinav, K. A.; Collu, Maurizio; Ke, Sun; Binzhen, Zhou (Volume 6: Ocean Space Utilization, 2019)
The aquaculture industry is being pushed into deeper waters, to accommodate the increasing demand for seafood worldwide and the lack of nearshore sites: aquaculture systems for farther, harsher conditions are now being proposed. The Blue Growth initiative by the European Union is also tuned in the same direction, with the focus being on developing ocean based resources, including energy and aquaculture, and finding synergies among them. The present work proposes a novel multi-purpose platform (MPP), by retrofitting a feed barge with a small wind turbine and energy storage system, able to provide sustainable energy to a reference offshore aquaculture farm. The requirements and constraints for such hybrid system are defined, as well as a set of keys load cases, and its performance are analysed in the frequency domain. Wave loads are modelled using linear potential theory, while from an aerodynamic point of view, only the maximum thrust at the wind turbine hub level is considered in the static stability analysis. With reference to stability criteria and dynamic analysis in frequency domain, the suitability of the proposed MPP to act as a source of feed storage and energy supply is established, showing this as a potentially suitable solution.